IMPLEMENTASI AL-MUSAQAH PADA PETANI SAWIT MENURUT PERSPEKTIF EKONOMI ISLAM DI DESA BAGAN NIBUNG KABUPATEN ROKAN HILIR RIAU - Heru Kurniawan; Syamsul Effendi; Nurhudawi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the implementation of the al-musaqah contract among oil palm farmers, analyze the profit-sharing system and the duration of the cooperation, and assess its conformity with Islamic economic principles in Bagan Nibung Village, Rokan Hilir Regency, Riau. This study employed a qualitative method with a descriptive-analytical approach. Seventeen informants were selected through purposive sampling, consisting of seven oil palm plantation owners, seven plantation managers, one religious leader, one community leader, and one village official. Data were collected through observation, interviews, and documentation. Data validity was examined through triangulation, persistent observation, and member checking, while data were analyzed through data condensation, data display, and conclusion drawing. The results indicate that the oil palm plantation management practices in Bagan Nibung Village have fulfilled the basic elements of an al-musaqah contract, including the presence of plantation owners, managers, plantation objects, management activities, mutual agreements, and profit sharing. The contracts are generally concluded verbally based on mutual trust and local customs. The profit-sharing arrangements commonly use a 50:50 or 60:40 ratio after deducting certain operational expenses. However, the allocation of expenses for fertilizers, herbicides, harvesting, and transportation, as well as the rights and obligations of the parties and the duration of the cooperation, are not always clearly determined. From an Islamic economic perspective, these practices are substantially compatible with the principles of mutual consent, justice, trustworthiness, and mutual assistance and provide benefits to both parties. Nevertheless, their administrative implementation has not fully complied with Islamic economic principles and may still contain elements of gharar or uncertainty. Therefore, written agreements, transparency regarding operational expenses, clarification of the parties’ rights and obligations, and a definite cooperation period are required.